The mismatch between the maturity structure of bank assets and liabilities in Polish listed banks and the Polish banking sector: an empirical study - Chaikovska, Ivanna (Niedopasowanie struktury terminowej aktywów i pasywów w polskich bankach giełdowych oraz polskim sektorze bankowym: analiza empiryczna, 2020)
The purpose of the article is to identify the problem of the mismatch between the maturity structure of assets and liabilities of the Polish banking sector and Polish listed banks. The article analyzes the maturity balance sheet structure of the Polish banking sector in 2010 and 2019 and Polish listed banks in 2019. The results of this analysis indicate a significant mismatch in the maturity structure of assets and liabilities of Polish banks and the need for a significant reconstruction of the structure of liabilities in the direction of their extension. Furthermore, the results of the analysis identify the most and the least secure Polish listed banks in terms of mismatches in the maturity balance sheet structure, as well as banks with opposite trends in the maturity structure compared to the Polish banking sector.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 9, s. 16-28
Keywords: banks; maturity structure of assets and liabilities; Polish listed banks; Polish banking sector; liquidity; balance sheet